Optimizing the Role of Dharma Abadi Bumdes in Apuan Village Through Village Regulations - Ni Made Puspasutari Ujianti; Ida Ayu Putu Widiati; Luh Putu Suryani; I Nyoman Gede Sugiartha; Ida I Dewa Ayu Mas Manik Sastri; Dewa Gede Agung Semarabawa; I Wayan Sunarta; Ayu Prasetya Dewi; IGAA Candra Ningrat (Community Service Journal of Law, 2022)
Apuan Village is one of the villages located in Susut District, Bangli Regency. Apuan Village is one of the villages in the Susut District, Bangli Regency, which is rich in springs that have their own beauty so that they are worthy of being developed as a tourist attraction. Among the attractions in Apuan Village which were developed as tourist destinations are the Tibumana and Tirta Payuk waterfalls, which in addition to having beautiful panoramas are also often used as places for traditional self-cleaning. The management of tourist objects in Apuan Village during 2017 to 2019 is still managed by groups and individuals, so it cannot be optimized to improve the welfare of the people of Apuan Village. For this reason, cooperation is needed through a tourism object management agreement involving BUMDes so that management will be more professional. In order for BUMDes to be able to manage tourism objects, a legal umbrella is needed so that if later on the management of tourism objects is subject to a levy, then the levy is not an illegal levy. The solution to overcome partner problems is to provide legal assistance and counseling related to the legal form of tourism object management development programs through BUMDes and the realization of harmonious working relationships in the development of tourism object management in Apuan Village.